2021
DOI: 10.1093/ofid/ofab513
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Choice of Prophylaxis on the Microbiology of Cardiac Implantable Electronic Device Infections: Insights From the Prevention of Arrhythmia Device Infection Trial (PADIT)

Abstract: Background The Prevention of Arrhythmia Device Infection Trial (PADIT) investigated whether intensification of perioperative prophylaxis could prevent cardiac implantable electronic device (CIED) infections. Compared with a single dose of cefazolin, the peri-operative administration of cefazolin, vancomycin, bacitracin and cephalexin did not significantly decrease the risk of infection. Our objective is to compare the microbiology of infections between study arms in PADIT. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“… 9 Although most CIED infections are believed to result from the device implantation procedure, the recent P revention of A rrhythmia D evice I nfection T rial (PADIT) of intensive antimicrobial prophylaxis showed no significant effect on the overall risk of infection over and above that provided by standard preoperative antimicrobial prophylaxis. 10 One proposed explanation for this finding is that the proportion of CIED infections that have their onset postimplantation may be greater than previously thought. 10 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… 9 Although most CIED infections are believed to result from the device implantation procedure, the recent P revention of A rrhythmia D evice I nfection T rial (PADIT) of intensive antimicrobial prophylaxis showed no significant effect on the overall risk of infection over and above that provided by standard preoperative antimicrobial prophylaxis. 10 One proposed explanation for this finding is that the proportion of CIED infections that have their onset postimplantation may be greater than previously thought. 10 …”
Section: Introductionmentioning
confidence: 99%
“… 10 One proposed explanation for this finding is that the proportion of CIED infections that have their onset postimplantation may be greater than previously thought. 10 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early infection was considered present if it occurred 3 months or earlier after the procedure, whereas delayed infection was categorized as occurring between 3 and 12 months after the procedure. The microbiology of pathogens causing CIED infections in PADIT has been previously reported …”
Section: Methodsmentioning
confidence: 99%
“…The most common types of microorganisms were S. aureus (35.9%) and CoNS (39.2%) with a low incidence of methicillin-resistant S. aureus (MRSA) in patients enrolled mainly from Canadian and Dutch centers. By contrast, a 2016 large single-center US study that included 816 consecutive patients undergoing device removal for confirmed infection showed that patients with CDIs due to MRSA were about 15% [ 22 ].…”
Section: Etiologymentioning
confidence: 99%